Propionate-induced synthesis of odd-chain-length fatty acids by Escherichia coli. - Ingram, L O (1977)
Exogenous propionate is incorporated in vivo by Escherichia coli as a primer to produce lipids with fatty acids of odd chain lengths. This provides a method for the specific labeling of the three terminal carbons in the fatty acyl chains of phospholipids.